Preparation, Characterization and Intermediate-Temperature Electrochemical Properties of Er3+-Doped Barium Cerate–Sulphate Composite Electrolyte - Fufang Wu (Materials, 2019)
In this study, BaCe0.9Er0.1O3−α was synthesized by a microemulsion method. Then, a BaCe0.9Er0.1O3−α−K2SO4−BaSO4 composite electrolyte was obtained by compounding it with a K2SO4−Li2SO4 solid solution. BaCe0.9Er0.1O3−α and BaCe0.9Er0.1O3−α−K2SO4−BaSO4 were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and Raman spectrometry. AC impedance spectroscopy was measured in a nitrogen atmosphere at 400−700 °C. The logσ~log (pO2) curves and fuel cell performances of BaCe0.9Er0.1O3−α and BaCe0.9Er0.1O3−α−K2SO4−BaSO4 were tested at 700 °C. The maximum output power density of BaCe0.9Er0.1O3−α−K2SO4−BaSO4 was 115.9 mW·cm−2 at 700 °C, which is ten times higher than that of BaCe0.9Er0.1O3−α.